A Comparison of In Situ Aircraft Measurements of Carbon Dioxide and Methane to GOSAT Data Measured Over Railroad Valley Playa, Nevada, USA - Tadic, J. M.; Loewenstein, Max; Frankenberg, Christian; Butz, Andre; Roby, Matthew; Iraci, Laura T.; Yates, Emma L.; Gore, Warren; Kuze, Akihiko (IEEE transactions on geoscience and remote sensing, 2014)
In this paper, we report the vertical profiles of CO 2 and CH 4 measured with a cavity ring-down spectrometer (CRDS) on a research aircraft from near-ground level to 8 km above mean sea level. The airborne platform employed in this paper is an Alpha Jet aircraft operated from NASA's Ames Research Center. Flights were undertaken to Railroad Valley, NV, USA, to coincide with overpasses of the Greenhouse Gases Observing Satellite (GOSAT). Ground-based CO 2 and CH 4 were simultaneously measured using CRDS, at the time and location of the airborne and satellite measurements. Results of three GOSAT coordinated aircraft profiles and ground-based measurements in June 2011 are presented and discussed in this paper. The accuracy of the CO 2 and CH 4 measurements has been determined based upon laboratory calibrations (World Meteorological Organisation traceable standard) and pressure/temperature flight simulations in a test chamber. The overall uncertainty for the airborne measurements ranged from 0.31 to 0.39 ppm for CO 2 and from 3.5 to 5.6 ppb for CH 4 . Our column-averaged CO 2 and CH 4 measurements, which include about 61% of the total atmospheric mass, are extrapolated, using different techniques, to include the remainder of the tropospheric and stratospheric CO 2 and CH 4 . The CO 2 data are then analyzed using the Atmospheric CO 2 Observations from Space 2.9 and 3.3 algorithms. For methane data, the RemoTeC v2.1 algorithm was used in its full physics setup. Column-averaged CO 2 and XCO 2 , measured by GOSAT and analyzed from our data, ranged from 388.1 to 396.4 ppm, and XCH 4 ranged from 1.743 to 1.822 ppm. The agreement of the satellite and aircraft CO 2 mixing ratios, as well as ground measurements, falls within the uncertainties of the methods employed to acquire these numbers.